(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the communication skills of doctors at Tay Nguyen University Hospital. Subjects and Methods: A cross-sectional descriptive study was conducted on 45 observed communication encounters between doctors and patients/family members during examination and treatment at Tay Nguyen University Hospital from January to June 2025. The unit of analysis was a communication encounter. Communication skills were assessed using a checklist developed by the research team based on communication literature and relevant domestic studies, then reviewed and unified before data collection. Data were collected through direct observation of each encounter by one trained researcher and grouped into: (1) basic communication skills, (2) communication situation-handling skills, and (3) patients’/family members’ immediate responses during the encounter. This study did not assess inter-rater reliability. Results: Among basic communication skills, the proportions rated as good were: eye contact 75.7%, appropriate use of gestures 55.0%, providing clear information 87.7%, appropriate tone of voice 96.0%, proper word usage 77.8%, empathy 77.0%, and listening ability 82.1%. For situation-handling communication skills, the proportions rated as good were: friendly greeting 53.3%, initiating communication 80.0%, re-explaining/responding when patients or family members did not understand 82.2%, confirming patient understanding 37.8%, confirming patient needs 35.6%, closing the conversation 42.2%, handling crying/non-cooperative patients 62.2%, handling patient mistakes 91.1%, handling staff mistakes 82.2%, handling complaints/conflicts 93.3%, and handling patient anxiety 91.1%. Conclusion: Doctors at Tay Nguyen University Hospital in 2025 showed uneven communication performance across domains. Strengths were observed in information provision, tone of voice, listening, and management of several difficult situations; however, limitations remained in friendly greeting, use of gestures, closing the conversation, confirming patient understanding, and clarifying patient needs.